Building general competencies of social work students through experiential learning process - Gudinavičius, Benas; Bubnys, Remigijus; Šimaitytė, Sandra (Social Welfare: Interdisciplinary Approach, 2019)
The article deals with the building of general competencies of social work students during the process of experiential learning. The article presents the analysis of a qualitative structured written reflections of social work students (N=11) and reveals which instrumental, interpersonal and systemic competencies of social work students were built while participating in the experiantal learning activities for one week.
Keywords: general competence; experiential learning; reflection